(untitled) (PANGEEA, 2025)
Evolution and prospects of global warming. Mutations affecting life on Earth planet, our appliance which is alarming in a dynamic transformation: Perform the greenhouse . Research shows that this rate is every chance that mankind will be faced with a dramatic situati in vain. Kyoto Protocol, the reference to environmental protection remains the only way to stop the release of poisons into the atmosphere to save the planet and the humanity default. Keywords: dynamic transformation, climactical changes, gobal temperature.